2018
DOI: 10.14814/phy2.13613
|View full text |Cite
|
Sign up to set email alerts
|

Human physiological and metabolic responses to an attempted winter crossing of Antarctica: the effects of prolonged hypobaric hypoxia.

Abstract: An insufficient supply of oxygen to the tissues (hypoxia), as is experienced upon high‐altitude exposure, elicits physiological acclimatization mechanisms alongside metabolic remodeling. Details of the integrative adaptive processes in response to chronic hypobaric hypoxic exposure remain to be sufficiently investigated. In this small applied field study, subjects (n = 5, male, age 28–54 years) undertook a 40 week Antarctica expedition in the winter months, which included 24 weeks residing above 2500 m. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…From earlier expeditionary studies the measured energy expenditure was found to be much higher than that predicted from activity scores 14 and a 60% increase was found in the BMR 15 which was attributed to increased thyroid activity. This increase in BMR is consistent with small levels of weight loss seen in men undertaking low levels of physical work whilst over-wintering in Antarctica 16 . In a recent analysis of energy expenditure and substrate utilisation on an all-male transantarctic expedition (Spear-17), we found that this 60% increase in BMR was consistent with an increase in the energy required for thermoregulation 17 .…”
supporting
confidence: 77%
“…From earlier expeditionary studies the measured energy expenditure was found to be much higher than that predicted from activity scores 14 and a 60% increase was found in the BMR 15 which was attributed to increased thyroid activity. This increase in BMR is consistent with small levels of weight loss seen in men undertaking low levels of physical work whilst over-wintering in Antarctica 16 . In a recent analysis of energy expenditure and substrate utilisation on an all-male transantarctic expedition (Spear-17), we found that this 60% increase in BMR was consistent with an increase in the energy required for thermoregulation 17 .…”
supporting
confidence: 77%
“…Cyclic protocols adopted a pattern of exposure to hypoxia followed by the same time course of exposure to normoxia, lasting 4 [63] and 5 h [64] per day. Six out of the ten studies in humans, included in this review, analysed the effect of sustained or cyclic hypoxia in healthy active [60,61,62,65,66] or sedentary adults [67]. Three studies [60,61,62] implemented sustained HC corresponding to periods of 16, 24 and 60 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto, this review has mostly examined the molecular response of bone cells to hypoxia. However, it is also pertinent to inspect the responses from the available in vivo studies (for a more compre- Long-term sustained exposure has been reported to reduce several indices of bone health (Basu et al, 2013(Basu et al, , 2014O'Brien et al, 2018;W. Wang et al, 2017) whereas shorter term sustained exposure appears less noticeable (Rittweger et al, 2016) (2013) monitored members of the Indian army exposed to real altitudes of 5,400 to 6,700 m over 4 months and W. Wang et al (2017) exposed rats to a simulated~6,000 m for 21 days.…”
Section: In Vivo Hypoxiamentioning
confidence: 99%
“…Long‐term sustained exposure has been reported to reduce several indices of bone health (Basu et al, 2013, 2014; O'Brien et al, 2018; W. Wang et al, 2017) whereas shorter term sustained exposure appears less noticeable (Rittweger et al, 2016). Bone's varied response to hypoxia may be a function of the oxygen concentration it receives.…”
Section: In Vivo Hypoxiamentioning
confidence: 99%